MORBILIDAD Y MORTALIDAD MATERNA Y PERINATAL DE LA DIABETES GESTACIONAL EN UNA POBLACIÓN MEXICANA - Vega-Malagón Genaro; Miranda-Salcedo Janette Palmira (European Scientific Journal, ESJ, 2014)
Introduction. Diabetes mellitus affects 2.7% of all pregnancies. 90% of these are gestational and 10% are pre-gestational. The importance of this fact is that it is associated with maternal and prenatal complications. General Objetive. To compare the maternal-perinatal morbidity and mortality of diabetic and non-diabetic patients. Material and methods. A case and control study was made of the medical records of diabetic and non-diabetic pregnant patients. The size of of the sampling (71 per group) was calculated using the formula for two populations. The sampling was by paired quota according to age. In both group socio-demographic, obstetrics background, complication and maternal-perinatal mortality variables were measured; via interruption of the birth. The type of diabetes mellitus was measured in the case studies. The analysis included descriptive statistics, odds ratio, and a 95% reliability interval, using an x2 and student t test. Results. The average age was 30.39 ±5.81. Predominant facts were marital status, living with the spouse, housewives and city dwellers (p>0.05). In the case group, there was 83.1% of gestational diabetes and 16.9% of pregestational diabetes. The variables that showed a significant statistical difference (p<0.05) were preeclampsia(OR:12.14, RI:1.508-97.766); arterial hypertension brought on by pregnancy(OR:4.77, RI:1.495-15.281); low weight for gestational age (OR:6.8,RI:0.796-58.102); macrosomia (OR:20.42, RI:4.595-90.798); respiratory stress (OR: 6.8,RI: 0.796-58.102) and cesarean section (OR:7.61,RI:3.88-17.12). Conclusions. Preeclampsia, arterial hypertension brought on by pregnancy, low weight for gestational age, macrosomia, respiratory stress and cesarean section were the chief complications for pregnant diabetic patients.